Source of Moral Knowledge - Gautam, Ayesha (Tattva Journal of Philosophy, 2023)
One cannot deny the fact that we all have some understanding of moral issues. Each one of us can be said to have some sense of what is right, what is wrong, what is good, what is bad, what ought to be done, and what ought not to be done. This moral understanding can be in the form of some vague idea, notion, or simply a gut feeling. No matter who the person is, from which culture or community the person belongs to, everybody faces a moral quandary sometime or other in one’s life. All of this presupposes that there is some fundamental sense or understanding of what is right and what is wrong. We all seem to have some understanding about actions that are right and those that are wrong. Some actions, for instance, torturing babies just for fun, killing an innocent person, raping, etc. are exemplars of morally wrong actions. Assisting a person in need, giving to famine relief, etc. on the other hand are examples of morally right actions. The present essay is an attempt to delve into the question of the source of moral knowledge. Three sources, experience, reason, and intuition have been identified. Views of philosophers like G.E Moore, WD Ross, Immanuel Kant, JS Mill, Plato, Samuel Clarke, Aristotle Hume, and Anthony Ashley Cooper have been discussed to gain clarity about the issue.